Preoperative Left Ventricular Global Longitudinal Strain Identifies Aortic Stenosis Patients with Improved Postoperative Recovery of Left Ventricular Geometry: A Prospective Cohort Study - Zafirovska, Planinka; Rodney Alexander, Rosalia; Georgievska-Ismail, Ljubica; Matveeva, Niki; Mitrev, Zhan (Brazilian Society of Cardiovascular Surgery (Sociedade Brasileira de Cirurgia Cardiovascular - SBCCV), 2022)
Abstract Introduction: The left ventricular ejection fraction (LVEF) is commonly used as a marker of aortic stenosis (AS) disease severity and to indicate surgical intervention. However, an LVEF <50% identifies mainly advanced disease. Hence, earlier detection of subclinical LV systolic dysfunction may improve clinical decision-making. The global longitudinal strain (GLS) can identify subclinical systolic dysfunction at earlier stages of AS progression even in the presence of preserved LVEF. To this end, we evaluated the preoperative prognostic significance of the LVGLS to identify patients who will undergo a more extensive postoperative LV reverse remodeling as a surrogate marker for clinical recovery. Methods: We performed a prospective observational study based on detailed pre- and postoperative 2D transthoracic echocardiographic examinations, including strain analysis with speckle tracking. We screened 60 consecutive patients with severe AS and a preoperative LVEF ≥50% indicated for surgery; 39 patients met the study entry criteria and consented to their participation. Results: The median age was 67 (range 30-79) years; 56.4% were female. At baseline, the GLS was 61.64±7.22%. Surgery led to an improvement in the GLS; the mean difference was 3.23% [95% CI=1.96 to 4.49%] during a median follow up time of 5 (interquartile range 4-6) months. The preoperative GLS correlated with the postoperative LV mass index (LVMI) r=0.526, P=0.001 and the intraventricular septal thickness in diastole (IVSd) r=0.462, P=0.003. Furthermore, patients with a normal GLS (≤-18.9%) at baseline experienced a better recovery of their LV morphology and systolic function during the postoperative course compared to those with an abnormal GLS (>-18.9%). The effect size, hedges g, was at least >0.75 for the LVMI, IVSd, intraventricular septal thickness in systole (IVSs), left ventricular posterior wall thickness in diastole (LVPWd) and LVEF, suggesting a clinically significant difference between subgroups at follow-up. Conclusion: A normal preoperative left ventricular global longitudinal strain is associated with an improved left ventricular reverse remodeling and systolic function following surgery to resolve aortic stenosis.
Keywords: Aortic Valve Stenosis; Biomarkers; Clinical Decision-Making; Echocardoography; Heart Ventricules; Severity of Illness Index; Ventricular Remodeling